TRANSFORMASI TEKNOLOGI PEMBELAJARAN DALAM IMPLEMENTASI KURIKULUM MERDEKA DI MIN 3 SUBANG - Omang Komarudin; Miptah Parid; Muchamad Riffki; Lukman Nugraha; Miftachul Huda (Al-Aulad: Journal of Islamic Primary Education, 2025)
This article aims to discuss the transformation of learning technology in the implementation of the merdeka Curriculum at MIN 3 Subang. This study employs a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results show that technological transformation in the implementation of the merdeka Curriculum has had a positive impact on three main aspects: learning media, learning resources, and assessment. In the aspect of learning media, teachers utilize instructional videos from YouTube and interactive PowerPoint presentations with images and audio to create engaging and easily understandable learning experiences. In terms of learning resources, students access digital platforms such as youTube, e-learning platform, articles, and e-books to support independent learning based on their interests and abilities. Meanwhile, in the aspect of assessment, teachers use google forms for daily, midterm, and final assessments, with results obtained automatically, as well as quizizz for formative assessments designed as interactive and enjoyable games. In conclusion, the technological transformation at MIN 3 Subang has successfully integrated digital media, learning resources, and assessments synergistically, thereby supporting the implementation of the merdeka Curriculum that is adaptive, creative, and relevant to technological developments and the needs of today’s learners.